PENGARUH KARAKTERISTIK DEWAN DIREKSI DAN UKURAN DEWAN DIREKSI TERHADAP NILAI PERUSAHAAN DI SEKTOR PROPERTI - Dhea Ayu Puspita Sari; Rahman Anshari; Muhammad Iqbal Pribadi (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the effect of board characteristics and board size on firm value in the property sector listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The research method used is quantitative with a causal approach. The sampling technique used purposive sampling and resulted in 273 firm-year observations. The dependent variable used is firm value as measured using the Price to Book Value (PBV) ratio, while the independent variables consist of board characteristics and board size. Data is obtained through documentation from the company's annual report. Data analysis was conducted with multiple linear regression and classical assumption tests. The results showed that the characteristics of the board of directors have no significant effect on firm value. Meanwhile, board size has a significant negative effect on firm value. The low coefficient of determination (adjusted R²) of 1.3% indicates that the independent variables only explain a small part of the variation in firm value. These findings suggest that the effectiveness of corporate governance is not solely determined by the characteristics or number of board members, but is also influenced by other external factors and operational performance. This study provides implications for company management and investors to be more selective in assessing board structure and its impact on firm value.